Recent progress on the application of molecular spectroscopic and chromatographic methods for analysis of Halal and Kosher gelatins in food and pharmaceutical products - Abdul Rohman,, Anjar Windarsih, Ida Musfiroh, Vevi Maritha, Wirnawati, Dwi Lestari, Dachriyanus Hamidi, Yugo Susanto, Nor Kartini Abu Bakar (Journal of Applied Pharmaceutical Science, 2025)
Gelatin can be obtained by hydrolysis of collagen partially from the skin, bone, and connective tissues of animals in acid or basic conditions, and is a functional ingredient widely used in some products which are related to food, cosmetics, and pharmaceuticals. The most common gelatins found in these products are bovine gelatin (BG), porcine gelatin (PG), and recently fishes-based gelatin was also developed. However, unclear labelling and false composition related to gelatin sources in products are serious issues, especially for some Muslims who have the faith that PGs are nonhalal. Therefore, the accessibility of reliable methods capable of identifying the gelatin types in the products is very urgent. Due to its simplicity, molecular-spectroscopic methods are proposed, developed, and validated for the detection of gelatins. In addition, the chromatographic-based methods especially hyphenated with mass spectrometers such as Liquid chromatography tandem mass spectrometry are capable of separating and identifying the gelatin sources through searching the specific markers in halal and nonhalal gelatins. The molecular spectra and chromatogram profiles of gelatins in complex sample matrixes have resulted in a huge number of data, therefore the employment of special statistical tools of chemometrics is unavoidable. This review highlighted the employment of molecular spectroscopy and chromatographic-based methods for the identification of gelatin sources and the authentication of gelatin sources and gelatin-based products (food, cosmetics, and pharmaceuticals). This review could provide analytical guidance and strategies for proposing and developing molecular spectroscopic and chromatographic-based techniques for the identification and authentication of gelatins.
Keywords: Porcine gelatin, multivariate data analysis, halal authentication analysis, FTIR spectroscopy, pharmaceutical products